Mechanical Noise Improves the Vibration Perception Threshold of the Foot in People With Diabetic Neuropathy. (January 2020) - Zwaferink, Jennefer B. J.; Hijmans, Juha M.; Schrijver, Claudia M.; Schrijver, Laura K.; Postema, Klaas; van Netten, Jaap J.
Background: Mechanical noise may improve somatosensation at the dorsal side of the foot, but the effect at the plantar side of the foot, the side most at risk for foot ulceration, is unknown. Moreover, techniques used in research so far have several problems that limit applicability in daily practice. Piezoelectric actuators may provide mechanical noise with better clinical applicability. We assessed the effects of piezoelectric actuators generating mechanical noise on the vibration perception threshold (VPT) at the plantar side of the foot in people with diabetic neuropathy. Methods: Double-blind within-subjects design in a controlled laboratory setting including participants with diabetic neuropathy (N = 40; 18 male; mean age 69.6 years; mean duration of diabetes 14.1 years; mean BMI 30.5). VPT was measured at three plantar foot locations with and without mechanical noise applied via piezoelectric actuators. Results: Mechanical noise improved VPT at metatarsophalangeal joint (MTP) 1 (left 39.3V vs 43.5V; right 39.0 vs 42.6 V), MTP5 (left 37.5V vs 41.7V; right 34.5V vs 40.8V) and the heel (left 40.0V vs 44.0V; right 39.3V vs 41.0V), all P < .001. Conclusions: Mechanical noise improves VPT at the plantar side of the foot in people with diabetic neuropathy. This is an important step for further development of insoles using mechanical noise that may have the potential to improve VPT and decrease the risk of foot ulceration.